Small and Wide Angle X-Ray Scattering Studies of Biological Macromolecules in Solution - Liu, Li (MyJove Corporation, 2013)
In this paper, Small and Wide Angle X-ray Scattering (SWAXS) analysis of macromolecules is demonstrated through experimentation. SWAXS is a technique where X-rays are elastically scattered by an inhomogeneous sample in the nm-range at small angles (typically 0.1 - 5°) and wide angles (typically > 5°). This technique provides information about the shape, size, and distribution of macromolecules, characteristic distances of partially ordered materials, pore sizes, and surface-to-volume ratio. Small Angle X-ray Scattering (SAXS) is capable of delivering structural information of macromolecules between 1 and 200 nm, whereas Wide Angle X-ray Scattering (WAXS) can resolve even smaller Bragg spacing of samples between 0.33 nm and 0.49 nm based on the specific system setup and detector. The spacing is determined from Bragg's law and is dependent on the wavelength and incident angle. In a SWAXS experiment, the materials can be solid or liquid and may contain solid, liquid or gaseous domains (so-called particles) of the same or another material in any combination. SWAXS applications are very broad and include colloids of all types: metals, composites, cement, oil, polymers, plastics, proteins, foods, and pharmaceuticals. For solid samples, the thickness is limited to approximately 5 mm. Usage of a lab-based SWAXS instrument is detailed in this paper. With the available software (e.g., GNOM-ATSAS 2.3 package by D. Svergun EMBL-Hamburg and EasySWAXS software) for the SWAXS system, an experiment can be conducted to determine certain parameters of interest for the given sample. One example of a biological macromolecule experiment is the analysis of 2 wt% lysozyme in a water-based aqueous buffer which can be chosen and prepared through numerous methods. The preparation of the sample follows the guidelines below in the Preparation of the Sample section. Through SWAXS experimentation, important structural parameters of lysozyme, e.g. the radius of gyration, can be analyzed.